Extracellular Matrix Modulates Angiogenesis in Physiological and Pathological Conditions. (18th May 2014) - Neve, Anna; Cantatore, Francesco Paolo; Maruotti, Nicola; Corrado, Addolorata; Ribatti, Domenico
Abstract : Angiogenesis is a multistep process driven by a wide range of positive and negative regulatory factors. Extracellular matrix (ECM) plays a crucial role in the regulation of this process. The degradation of ECM, occurring in response to an angiogenic stimulus, leads to degradation or partial modification of matrix molecules, release of soluble factors, and exposure of cryptic sites with pro- and/or antiangiogenic activity. ECM molecules and fragments, resulting from proteolysis, can also act directly as inflammatory stimuli, and this can explain the exacerbated angiogenesis that drives and maintains several inflammatory diseases. In this review we have summarized some of the more recent literature data concerning the molecular control of ECM in angiogenesis in both physiological and pathological conditions.